Political Business Cycles with Endogenous Election Timing: Evidence from Japan - Cargill, Thomas F.; Hutchinson, Michael M. (The Review of Economics and Statistics, 1991)
Thomas F. Cargill, Michael M. Hutchinson, Political Business Cycles with Endogenous Election Timing: Evidence from Japan, The Review of Economics and Statistics, Vol. 73, No. 4 (Nov., 1991), pp. 733-739